2012
DOI: 10.29173/lirg499
|View full text |Cite
|
Sign up to set email alerts
|

The collection and analysis of job advertisements: A review of research methodology

Abstract: An increasing number of research studies in LIS use job adverts as a data source to analyse and track changes to job skills and the employment market over time. This review of 70 research studies in LIS aims to provide an overview of key characteristics of existing research methods, and to suggest improvements which could be made to methods. The researcher analysed different aspects of each study using a quantitative approach, and noted salient features of each study’s methodology. The review found that stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 66 publications
0
82
0
4
Order By: Relevance
“…Manual coding has been the preferred method for most of the studies in the past because it allows the researcher to frame the coding within a context (Harper, 2012). The coding scheme started to be developed at this stage and included about 20% of the data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual coding has been the preferred method for most of the studies in the past because it allows the researcher to frame the coding within a context (Harper, 2012). The coding scheme started to be developed at this stage and included about 20% of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Harper (2012) stated that studies that examine job ads are particularly relevant for positions in areas outside the traditional LIS roles, like knowledge management (KM). Two earlier studies found that the majority of positions advertised required an ALA accredited master degree (Wright, 1988) and that public service positions required more advanced degrees while technical positions required more computer skills (Reser & Schuneman, 1992).…”
Section: Changing Job Descriptionsmentioning
confidence: 99%
“…Next, the authors collected position descriptions using purposive sampling to ensure the job postings fit the criteria. Purposive sampling, selecting the sample based on specific characteristics, is a commonly used technique for studying job announcements (Harper 2012).…”
Section: )mentioning
confidence: 99%
“…There are increasing numbers of studies, especially in information science fields, that use job advertisements as research data sets. The primary purpose of these studies is to examine change in skill requirements and to identify currency of skills in the workplace [14]. Many studies have used job advertisements as data sources to identify skills and competencies since the advertisements offer various sources of information on the main competencies.…”
Section: Job Ads As Research Datamentioning
confidence: 99%
“…In other words, advertisements contain adequate information for analyzing and extracting job competencies. Job advertisements contain an up-to-date set of skills that reflect not only the requirements set by the industry, but also current employment environments and development in the labor market [14], [17].…”
Section: Job Ads As Research Datamentioning
confidence: 99%